Tokyo ESP. 8 - Segawa, Hajime (Vertical, Inc., 2017)
"Once the board members of Ares have gathered, Claudia uses Touko to awaken the Messiah and receive its benediction—a massive magnification of her ESP—just as Rinka, Kobushi, Minami and Nadja storm in, setting off the biggest ESP battle in Tokyo’s history. Then an old enemy shows up, and alliances are strained as allegiances are tested. Can Rinka and her friends take down the power-drunk Claudia before Tokyo is wiped off the map...?"--Back cover.